Forms of Librarians' Communication and Their Impact on User Satisfaction in The IAIN Kediri Library - Moch. Basit Aulawi; Mustajib (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
This study aims to see the extent of the librarian's form of communication and its impact on user satisfaction in the IAIN Kediri Library. The theory used is librarian communication and user satisfaction. Using a qualitative approach, this study resulted in the conclusion that the form of communication of IAIN Kediri librarians was very good and had a good impact on users. The majority of users feel that librarians are always fast and responsive in assisting students in finding information in the library, librarians prioritize the interests of students who need help, librarians are willing and patient in serving students, librarians do circulation services well, and librarians provide services according to the promised time